Peningkatan Hasil Belajar IPS Dengan Menerapkan Model Picture And Picture Siswa Sekolah Dasar - Novrianti Yusra; Indriyanto Indriyanto (Jurnal Pendidikan Tuntas, 2023)
The aim of this researchis to describe the application of picture and picture model to improvethe learning outcomes of the knowing currency history at class III SDN 009 Ganting Salo district. The formulation of the problem in this research is how the application of picture and picture model to improve learning outcomes on the material of knowing currency history at class III SDN 009 Ganting Salo district. This research was conducted in class III SDN 009 Ganting Salo district. This research was conducted in two cycles and each cycle was held twice. The subject of this research is the students of class III SDN 009 Ganting Salo district which amounted to 18 people, with the number of male students 9 people, and female students 9 people. The techniques of collection Data used in this research are of observation, documentation, and evaluation. Based on the research results can be concluded that in the first cycle is still quite good with an average of 65,28. Then from 18 students only 11 students or 61,11% who achieve mastery individually. Students' learning outcomes in cycle II is quite good with an average of 71,94, and 15 students complete or 83,33% who achieve mastery individually. Thus it can be concluded that with the implementation of picture and picture model can be improve the learning outcomes of the knowing currency history at class III SDN 009 Ganting Salo Kampar district.